Creating the suburban school advantage : race, localism, and inequality in an American metropolis - Rury, John L., 1951- (Histories of American education, 2020)
"This book describes how an ethos of localism and racial exclusion created a perceived and real advantage for suburban school districts in the postwar era, focusing on developments in metropolitan Kansas City"--